Genetic analysis of the Hel308 helicase in the archaeon Haloferax volcanii - Gamble-Milner, Rebecca (2016)
Hel308 is a RecQ family DNA helicase that is conserved in metazoans and archaea but is absent from bacteria and fungi. Hel308 family helicases are implicated in DNA repair, homologous recombination and genome stability, but the exact role of Hel308 is largely unknown. Strains deleted for hel308 are sensitive to DNA inter-strand crosslinks, which are potent blocks to DNA replication. In this study, the archaeon Haloferax volcanii was used as a model organism to study the role of Hel308.